Competency Development of Operational Personnel at Mirah and Berlian Terminals Through Spinner Reborn System Training to Support Container Loading and Unloading Performance - Choirul Anam; Suryanto Suryanto (Jurnal Ilmiah Sumber Daya Manusia, 2022)
Research Competency Development on employees in the Terminal Rubies and Diamonds with a system of training a spinner reborn is made to analyze and describe explicitly, with regard to the development of competence to improve the performance of the operational employees, including the ability to adapt to be able to develop the ability and adjustment themselves with the era of business transformation in the digital. The study was conducted by using the descriptive qualitative method to determine the analysis of the results, where the collection of primary data in this research is done by observation, interview, survey and expert justification, while the secondary data is done through the duties and responsibilities of work to be done with the population research using purposive sampling method which is taken from the employee homogeneously in the accept, perform and megimplementasikan the activities of the development of these competencies. The application of training in the implementation of operations related to loading and unloading the container is intended to provide structuring the completion of the work proper with the interconnectedness of all areas of work and also a system of spinner reborn existing in the process of loading and unloading the container.